2018
DOI: 10.1186/s40708-018-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Various epileptic seizure detection techniques using biomedical signals: a review

Abstract: Epilepsy is a chronic chaos of the central nervous system that influences individual’s daily life by putting it at risk due to repeated seizures. Epilepsy affects more than 2% people worldwide of which developing countries are affected worse. A seizure is a transient irregularity in the brain’s electrical activity that produces disturbing physical symptoms such as a lapse in attention and memory, a sensory illusion, etc. Approximately one out of every three patients have frequent seizures, despite treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…In the literature, the amplitude of the signal, the distance between seizure and nonseizure intervals and the energy ratio of EEG have been investigated. These studies have been used as a criterion for the evaluation of epileptic activity [43][44][45][46][47]. Today, many mathematical methods are used in the analysis of EEG data [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the amplitude of the signal, the distance between seizure and nonseizure intervals and the energy ratio of EEG have been investigated. These studies have been used as a criterion for the evaluation of epileptic activity [43][44][45][46][47]. Today, many mathematical methods are used in the analysis of EEG data [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after applying the models on the signal we have a simple, reduced but more assertive signal for analysis, which gives best insight into the signal. In literature survey we have found that recent research in signal processing is surrounding around very famous transformations like wavelets, EMD, Fourier, Hilbert and Fast Fourier etc [17]. Therefore there is a need of adaptive methods and transformations which can solve the signal processing problems efficiently and we believe that using adaptive methods and transformations on these selected signals can perform better than all other existing methods.…”
Section: Methodologies Usedmentioning
confidence: 99%
“…A rectangular 1 sec (250 samples, over sampled to 256) long window is used for windowing the halfwave. Window size used here is 1 second [32] [17] for both time domain and frequency domain is considered as a best size window. Time domain features like total number of extrema points, slopes of extrema points, maximum of slopes, mean of extrema points, minimum of extrema points, maximum of extrema points have been chosen from each1-s-long window after analyzing their properties by means of histograms.…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy is one of the most common neurological conditions, with more than 2% of the population worldwide affected according to the latest study [1]. As a chronic disease, epilepsy requires long-term treatment with anti-epileptic drugs (AEDs) [2].…”
Section: Introductionmentioning
confidence: 99%